Pengaruh Perceived Risk Dan E-Service Quality Terhadap Customer Loyalty Dengan Switching Cost Sebagai Variabel Mediasi Di Zalora - Utami, Abigail Setyo; Ellitan, Lena; Supriharyanti, Elisabeth (Kajian Ilmiah Mahasiswa Manajemen, 2017)
People in the current era tend to use technology to fullfil their needs in shopping. From that it raises, the number one of online retailers use it to open an online stores. There are many cases of fround an uncomfortable service in the online shop, it makes people more worried to shopping. This research is intend to know the effect of perceived risk and e-service quality to customer loyalty through switching cost. In this research, the four variable are analyzed using SEM analysis through SEM asumption test with Lisrel program. The population of this research is all of people who have shopping in Zalora and the number of samples of this research is 150 respondend who spread around Surabaya. The object of this research is Zalora online stores. The technique used in this research is Non Probability Sampling technique with incidental method. The result of this research show that switching cost can mediated e-service quality in customer loyalty.